Meningkatkan Kemampuan Siswa Kelas IX B dalam Memahami Sistem Reproduksi Manusia melalui Model Kooperatif di SMPN 2 Angkinang - Muhammad Hasnan Fauzi (Universitas Sebelas Maret, 2018)
Science lesson in class IX B SMPN 2 Angkinang in semester 1 one of them is Human Reproduction System. But there are problems that are experienced by students is on aspects of students' ability in understanding this material. The ability of students in class IX B SMPN 2 Angkinang in understanding the Human Reproduction System is still very low. Departing from these problems, science teachers then try to improve students' ability in understanding the Human Reproduction System. One way that can improve students' ability in understanding the Human Reproduction System is to use cooperative models. The model focuses on the use of small groups of students to work together in maximizing learning conditions to achieve learning objectives. Therefore, classroom action research needs to be done to improve students ability of class IX B in understanding human reproduction system through cooperative model in SMPN 2 Angkinang. This research was conducted with two cycles consisting of 4 times meeting by using cooperative model which have positive impact for learning process of science subjects especially on the material of Human Reproduction System. It is proven by the average score of students from pre cycle 70.4 in cycle 1 increased to 77.6 and in cycle 2 increased to 87.3. Thus it can be concluded that there is an increase in the ability of students to understand the Human Reproductive System in Students Class IX B SMPN 2 Angkinang.